Determinants of Profitability of Banking Companies Listed on the IDX for the 2020-2024 Period - Febriani, Sherli Putri; Handriani, Eka; Rahayu, Sri (Dinasti Publisher, 2026)
This study examines the effect of Non-Performing Loans (NPL), Operating Expenses to Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Firm Size on the profitability of banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Secondary data were obtained from 42 banks selected through purposive sampling, resulting in 210 observations. Multiple linear regression analysis was conducted using SPSS version 25. The results show that NPL and BOPO have a significant negative effect on bank profitability, indicating that higher credit risk and operational inefficiency reduce profits. Conversely, LDR and Firm Size have a significant positive effect, suggesting that effective fund utilization and larger business scale contribute to higher profitability. Simultaneously, these four variables explain 51.4% of the variation in bank profitability. The findings highlight the importance of strengthening credit risk management and improving operational efficiency to support sustainable and stable financial performance, particularly amid the dynamic conditions of Indonesia’s banking industry.